2014
DOI: 10.1155/2014/351248
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Gellan Gum Film Containing Virgin Coconut Oil for Transparent Dressing Materials

Abstract: We examined the potential of virgin coconut oil (VCO) incorporated in gellan gum (GG) films as a dressing material. Pure GG film is extremely brittle and inclusion of 0.3% (w/w) VCO in the GG film (GG-VCO3) improved the toughness (T≈0.67±0.33 J g−1) of the composite films. Swelling properties and water vapor transmission rates of GG-VCO composite films decreased, whereas thermal behavior values increased upon the addition of higher concentrations of VCO. Cell studies exhibit that the VCO is noncytotoxic to hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…13 The physical and mechanical properties, including hardness and roughness of hydrogel containing clays could be another reason cells were dying. 17,42 In addition, the solubility of clays in biopolymer solutions also plays an important role which may influence the growth of cell as reported by a previous study. 30 They demonstrated that the reduction of weight percentage of polyethylene glycol (PEG) in polypeptide-PEG exhibits better cell adhesion.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…13 The physical and mechanical properties, including hardness and roughness of hydrogel containing clays could be another reason cells were dying. 17,42 In addition, the solubility of clays in biopolymer solutions also plays an important role which may influence the growth of cell as reported by a previous study. 30 They demonstrated that the reduction of weight percentage of polyethylene glycol (PEG) in polypeptide-PEG exhibits better cell adhesion.…”
Section: Resultsmentioning
confidence: 82%
“…It is also used as a scaffold material for tissue engineering application. 14,15 GG has been reported to have good biocompatibility on mouse fibroblast cells (L929), 16 human skin fibroblast cells (CRL2522), 17 and human fetal osteoblasts (hFOBs 1.19). 18 In general, hydrogel can be classified as a three dimensional polymer network which has received more attention in past decade due to its ability to absorb and retain high amount of water.…”
Section: Introductionmentioning
confidence: 99%
“…GG has a broad band at 3476 cm −1 , which is a typical region for stretching of the O-H group (3000–3500 cm −1 ) [ 27 ]. A new distinguishing peak observed at 1638–1675 cm −1 in GVCO hydrogels correlates to the shifting of -C-H (-CH 2 ) bending scissoring of VCO and C=C due to the appearance of phenolic content and stretching of that aromatic ring [ 28 ]. The stretching alkyl signal in VCO microemulsion at 2943 cm −1 shifted to 2930–2920 cm −1 in GVCO hydrogels confirming the hydrogen bonding interaction in GVCO blends [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…This facilitates the tight packaging of gellan gum chains, resulting in fragile hydrogels. However, the addition of VCO microemulsion that contains lauric acid (C12 ≈ 78%) and a hydroxyl group is responsible for promoting the formation of hydrogen bonds between gellan gum and VCO microemulsion [ 28 ]. This bonding replaces the hydrogen bonds between gellan gum chains and thus decreases the intermolecular bonds along polymer chains and improves strain-at-break [ 6 ] of the hydrogels regarding the content of VCO microemulsion.…”
Section: Resultsmentioning
confidence: 99%
“…GG is an anionic straight chain biopolymer containing β-D-glucose, α-L-rhamnose and β-D-glucuronate residues 1 and usefulness industrially due to its unique structure and physical properties. Previously, GG has been approached in wound healing study 2,3 as well as candidate material for tissue engineering application 4 and hold a vital role in pharmaceutical. Since 1992, this materials were approved to be utilized in food industry by the US FDA (United States Food and Drug Administration) and the EU (European Union) regulation classified as E 415 5 .…”
Section: Introductionmentioning
confidence: 99%